Scientific communication of research results in the Cienfuegos Medical Sciences University teachers - Yuleydi Alcaide Guardado; Rosmery Ortega Consuegra; Belkis González Aguiar; Enrique Acosta Figueredo; Juan Luis Vidal Martí; Mabel Rocha Vázquez (Medisur)
Foundation: in the universities context, scientific communication plays a fundamental role. Teachers, researchers and scientists are key subjects in the knowledge dissemination and diffusion. Objective: to describe the teachers’ scientific production at the Cienfuegos Medical Sciences University. Methods: descriptive and cross-sectional study during the studied period from January 2018 to December 2022. The universe consisted of 1,750 scientific articles registered in the scientific results database of the Cienfuegos Provincial Center for Information on Medical Sciences, and the sample was selected by simple random sampling at convenience, so that it was made up of 806 scientific articles. Results: of the total of 806 scientific results, 421 were published in scientific journals, and 385 in events. In 2020, publications in journals in collaboration with other institutions predominated (65.3%). Regarding collaboration with national institutions, the University of Cienfuegos, the National School of Public Health and the Central University of Las Villas stood out. Collaboration with foreign institutions was most frequently developed with Spain. Conclusions: it is necessary to design strategies to strengthen the development of scientific communication of research results among teachers. This results in increased scientific visibility and international recognition of the researchers and their university.